Hot Deformation Behavior, Processing Maps, and Microstructure Evolution of 7E97 Alloy - Fangyan He; Xiaolan Wu; Shengping Wen; Liang Hong; Zhizheng Rong; Hanyu Chen; Kunyuan Gao; Wu Wei; Hui Huang; Zuoren Nie (Metals)
A hot compression simulation was conducted on the Al-7.62Zn-2.22Mg-0.90Cu-0.30Mn-0.09Er-0.13Zr alloy (7E97) within the temperature range of 300~460 °C and strain rate range of 0.001~10 s−1 using a Gleeble-3500 hot simulator. A flow-stress constitutive equation and hot processing maps were established for the alloy, and the microstructural evolution of the alloy after hot deformation was investigated. It was found that the dominant dynamic softening mechanism of the alloy was dynamic recovery, accompanied by minor dynamic recrystallization. The optimal hot processing window for the alloy was determined to be in the ranges of 0.001~0.05 s−1 and 350~410 °C.